Botanical Cosmeceuticals for skin care - Kumar, Rajesh (International Journal of Pharmaceutical & Biological Archive, 2017)
Currently a new term in the cosmetic industry is ’Cosmeceuticals’, which is the fastest growing segment of the natural personal care trade. They are the next generation of skin care. ’Cosmeceuticals’ are the advances made within the world of skin products and the new paradigm in skincare. All cosmeceutical claims to contain functional ingredients with either therapeutic, disease-fighting or healing properties. There is no regulatory category for Cosmeceuticals; hence this review tries to understand regulatory scenario as well the difference between drug and cosmetics is enlightened. The paper is an earnest endeavor for commonly use of botanicals as skin cosmeceutical, classification of cosmeceutical, examples of some most important Botanicals for skin care and other cosmeceutical product that claims a beneficial physiologic effect. This review paper is to give recent knowledge about the latest trend of botanical Cosmeceuticals and their advantages over synthetic cosmetics.